2017
DOI: 10.1155/2017/1230713
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Insulin Levels and Nonpsychotic Dementia: A Systematic Review and Meta-Analysis

Abstract: Objectives To explore the relationship between insulin levels and nonpsychotic dementia. Methods Six electronic databases (PubMed, Cochrane, SCI, CNKI, VIP, and Wanfang) were searched from January 1, 2007, to March 1, 2017. Experimental or observational studies that enrolled people with nonpsychotic dementia or abnormal insulin levels in which insulin levels or MMSE scores (events in nonpsychotic dementia) were the outcome measures. Random-effects models were chosen for this meta-analysis. Sample size, mean, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…These are present particularly in areas associated with memory and learning, including the hypothalamus, amygdala, hippocampus, caudate and putamen . A recent meta‐analysis looking at the relationship between insulin levels and dementia found that blood insulin levels may increase in patients with non‐psychotic dementia . Additionally, changes in insulin levels also affect uptake of glucose by neurones and its metabolism via GLUT 4 pathways involved in cognition …”
Section: Insulin In the Brainmentioning
confidence: 99%
“…These are present particularly in areas associated with memory and learning, including the hypothalamus, amygdala, hippocampus, caudate and putamen . A recent meta‐analysis looking at the relationship between insulin levels and dementia found that blood insulin levels may increase in patients with non‐psychotic dementia . Additionally, changes in insulin levels also affect uptake of glucose by neurones and its metabolism via GLUT 4 pathways involved in cognition …”
Section: Insulin In the Brainmentioning
confidence: 99%